EDUKASI DAN PROMOSI KESEHATAN DALAM UPAYA PENCEGAHAN DAN PENGENDALIAN PENYAKIT TIDAK MENULAR DI DESA TAGALAYA KECAMATAN TOBELO - Olivia Asih Blandina; Ribka Yulianti Hohedu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2024)
This community service was carried out for 1 day in the community of Tagalaya Village, Tobelo District, which aims to educate and promote health in an effort to prevent and control non-communicable diseases. This activity was carried out by lecturers and students of the Nursing Study Program, Hein Namotemo University. The methods used are counseling and health checks. The implementation stage begins with counseling about non-communicable diseases delivered by students from the Nursing study program at Hein Namotemo University, which is followed by discussion and questions and answers. Then continued with cholesterol health checks on 67 people. The results of the health examination showed that 47 people in Tagalaya Village, Tobelo District had high cholesterol levels. The results of community outreach activities have increased knowledge or ability to understand the meaning, causes, treatment and prevention of non-communicable diseases.